RNA Vaccines against Infectious Diseases: Vital Progress with Room for Improvement - Hana M. Abdelzaher (MDPI AG, 2021)
mRNA vaccines have amassed a strong interest from scientists and nonscientists alike for their potential in treating cancer and curbing the spread of infectious diseases. Their success has been bolstered by the COVID-19 pandemic as mRNA vaccines for the SARS-CoV-2 virus showed unrivaled efficiency and success. The strategy relies on the delivery of an RNA transcript that carries the sequence of an antigenic molecule into the body’s cells where the antigen is manufactured. The lack of use of infectious pathogens and the fact that they are made of nucleic acids render these vaccines a favorable alternative to other vaccination modalities. However, mRNA vaccination still suffers from a great deal of hurdles starting from their safety, cellular delivery, uptake and response to their manufacturing, logistics and storage. In this review, we examine the premise of RNA vaccination starting from their conceptualization to their clinical applications. We also thoroughly discuss the advances in the field of RNA vaccination for infectious diseases. Finally, we discuss the challenges impeding their progress and shed light on potential areas of research in the field.